ANALYSIS OF CORPORATE GOVERNANCE PRINCIPLES IN FAILURE OF PAY OF PT ASURANSI JIWARA - Subekti, Muhammad Fauzan Abimanyu (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
This study aims to analyze the violation of corporate governance principles in the case of alleged corruption at PT Asuransi Jiwasraya (Persero), which is estimated to have caused losses of up to IDR 17 trillion. The type of research used is qualitative research with a descriptive research design. This study focuses on an in-depth analysis of corporate governance failures at PT Asuransi Jiwasraya by examining it as a case study. The research utilizes a content analysis approach and relies on secondary data sources, including previous studies, internet searches, financial reports, and other credible sources. The findings of this study reveal significant breaches in the application of the five core principles of good corporate governance transparency, accountability, responsibility, independence, and fairness. These principles are essential for guiding companies towards effective and ethical management practices, and their violation in the case of PT Asuransi Jiwasraya has led to severe financial repercussions and loss of public trust.